A subtle relationship between substrate stiffness and collective migration of cell clusters. Issue 7 (23rd January 2020) - Balcioglu, Hayri E.; Balasubramaniam, Lakshmi; Stirbat, Tomita Vasilica; Doss, Bryant L.; Fardin, Marc-Antoine; Mège, René-Marc; Ladoux, Benoit
Abstract : The physical cues from the extracellular environment mediates cell signaling spatially and temporally. Abstract : The physical cues from the extracellular environment mediates cell signaling spatially and temporally. Cells respond to physical cues from their environment in a non-monotonic fashion. Despite our understanding of the role of substrate rigidity on single cell migration, how cells respond collectively to increasing extracellular matrix stiffness is not well established. Here we patterned multicellular epithelial Madin–Darby canine kidney (MDCK) islands on polyacrylamide gels of varying stiffness and studied their expansion. Our findings show that the MDCK islands expanded faster with increasing stiffness only up to an optimum stiffness, over which the expansion plateaued. We then focused on the expansion of the front of the assemblies and the formation of leader cells. We observed cell front destabilization only above substrate stiffness of a few kPa. The extension of multicellular finger-like structures at the edges of the colonies for intermediate and high stiffnesses from 6 to 60 kPa responded to higher substrate stiffness by increasing focal adhesion areas and actin cable assembly. Additionally, the number of leader cells at the finger-like protrusions increased with stiffness in correlation with an increase of the area of these multicellular protrusions. Consequently, the force profile along the epithelial fingers in the parallel and transverse directions of migration showed an unexpected relationship leading to a global force decrease with the increase of stiffness. Taken together, our findings show that epithelial cell colonies respond to substrate stiffness but in a non-trivial manner that may be of importance to understand morphogenesis and collective cell invasion during tumour progression.